1867 Clinical outcomes for adolescents living with hepatitis B. (15th December 2022) - Fisayo, Temitope; Ragunahan, Sophie; Brown, Ashley; Tudor-Williams, Gareth; Foster, Caroline
Abstract : Objectives: 1) To audit clinical outcomes for adolescents living with chronic hepatitis B (CHB) 2) To audit clinical outcomes following transition to adult services Methods: Retrospective case note analysis extracting a dataset of all patients seen in the paediatric CHB clinic between 2010 and 2022. Data collated: e-antigen (eAg) status; e-seroconversion; alanine aminotransaminase (ALT); coinfection with hepatitis D virus (HDV), hepatitis C virus (HCV) or HIV; liver inflammation and fibrosis by transient elastography and biopsy; and treatment status for hepatitis B (HBV). Results: 58 children, 36 (62%) male, presented to paediatric CHB care. The median age at presentation was 13 years (IQR 6, 15). Ethnicity: Asian 25 (43%), black African 15 (26%), White 8 (14%), Other 3 (5%), Unknown 5 (9%). Viral co-infection: HDV (1), HIV (1) and HCV (0). 21 (36%) transitioned to adult services at a median age 18 years (IQR 18, 19), median length of time in adult care 4.6 years (IQR 3.1, 5.5), with no loss to follow up. At latest assessment; median age 18 years (IQR 12, 22): median ALT 38IU/L (IQR 24, 49) in paediatric care (n=37) and 44IU/L (IQR 29, 65) post-transition. 5 have ALT > twice upper limit of normal: 3 paediatrics; 2 adult care. 33/58 (57%) are eAg negative, 11 e-seroconverting during follow-up: in paediatrics (10) and post-transition (1). Median HBV DNA by HBeAg: positive 87, 000, 000IU/mL (IQR 20, 996, 641, 000, 000); negative 235IU/mL (IQR 33, 1537). Latest transient elastography mean CAP 198dB/m (SD ±57), mean E score 5.1kPA (SD ±1.7) with 5 having evidence of mild or severe fibrosis (F2 E score 7.4–11.1) 19 (33%) ever received HBV therapy, median age 14 years (IQR 8.5, 15); 1 treated post-transition aged 22. The pre-treatment median ALT 47IU/L (IQR 28, 64); median HBV DNA 401, 242IU/mL (IQR 635, 226, 500, 000). 15 received pegylated interferon alpha (PEG-IFNα); clinical trial (3), adult care (1). 3 stopped due to toxicity, including 1 post-transition. 4/15 (27%) e-seroconverted. 4/19 received tenofovir disoproxil fumerate: median age 14 years (IQR 14, 15); median HBV DNA 85, 003, 498IU/mL (IQR 6295, 579, 700, 000), with 2 achieving sustained viral suppression. 2/4 adolescents were eAg negative from treatment initiation. 11/58 underwent liver biopsy all pre-2018 in paediatric care. The modified Hepatic Activity Index (HAI) necroinflammatory scores median was 3/18 (range 1–8). The HAI fibrosis stage median 1/6 (range 1–3). 49/58 underwent transient elastography in paediatric services; mean CAP score 197dB/m (SD ±44), mean E score 5.4kPA (SD ±1.3). Three children had E scores >7.4kPA; all received treatment. Post-transition, 9/21 underwent transient elastography; mean CAP score 246dB/m (SD ±49). The mean E score was 5.9kPa (SD ±2.3) with two having E scores >7.4kPA; none has been treated. Conclusions: In this cohort of adolescents living with HBV rates of cirrhosis were reassuringly low. More than half had undergone e-seroconversion, all bar one prior to transition to adult care. One third e-seroconverted during follow up, the majority spontaneously. PEG-IFNα did not induce e-seroconversion in most cases when used.